A Call to Action for Intermediate and Secondary School Lifestyle Medicine Education: Instating Healthy Teen Behaviors. Issue 1 (January 2020) - Tollefson, Michelle; Kees, Alexandra; Bolze, Andrew; Wolferz, Richard; Plaven, Brittany; Frates, Elizabeth Pegg
Chronic diseases, previously thought to require decades of risk factors, have become increasingly prevalent in America's youth. National Health Education Standards have been published since 1995, and yet nearly a fifth of schools fail to follow any state or national health education guidelines. Utilizing the phrase "lifestyle medicine" in childhood would elevate the importance and standardization of the core health guidelines. Several independent pilot programs taught by undergraduate and medical student volunteers have successfully demonstrated lifestyle medicine education models at intermediate and secondary schools. Preliminary feedback demonstrates that student interest in and consideration of behavioral change is possible within this age group. As with any life stage, significant behavior change in youth requires strategic planning of authentic learning practices and culturally competent lessons. We argue for the interdisciplinary development and implementation of community-engaged lifestyle medicine education for intermediate and secondary schools as a promising intervention to address and reverse the chronic disease trend in our youth.